Chapter Foundations of Human and Animal Sensory Awareness: Descartes and Willis - Brown, Deborah (Knowledge and its Histories, 2023)
In arguing against the likelihood of consciousness in non-human animals, Descartes advances a slippery slope argument that if thought were attributed to any one animal, it would have to be attributed to all, which is absurd. This paper examines the foundations of Thomas Willis' comparative neuroanatomy against the background of Descartes' slippery slope argument against animal consciousness. Inspired by Gassendi's ideas about the corporeal soul, Thomas Willis distinguished between neural circuitry responsible for reflex behaviour and that responsible for cognitively or consciously mediated behaviour. This afforded Willis a non-arbitrary basis for distinguishing between animals with thought and consciousness and those without, a methodology which retains currency for neuroscience today.